Features of age-related dynamics of microstructure of mammary glands - Adamovych, O.O.; Chelpanova, I.V.; Paltov, Y.V.; Sopneva, N.B.; Poliiants , A.V. (Морфологія / Morphologia / Morfologìâ, 2023)
Background. Breast pathology holds a prominent place among the most frequently manifested pathologies in the female population worldwide. With the incidence rate reaching 70-75% in women of different age groups and showing a steady upward trend, the issue of early diagnosis is particularly relevant today. The final verification of the diagnosis of breast pathology involves conducting a histological slides, which requires a thorough understanding of the characteristics and variations in the normal structure of the mammary gland. From a morphological perspective, the mammary gland exhibits exceptional variability in its structure and a wide range of changes related to growth, formation, lactation, hormonal dynamics, and age. Objective. To study the characteristics of the structure of mammary glands in women of different ages. Methods. Histological sections of breast tissue with a thickness of 5±1 μm were placed on highly adhesive glass slides, dried, deparaffinized, and rehydrated according to accepted standards. The slides were examined under a UlabXSP-137TLED microscope at various magnifications and photographed using an XCAM 1080P camera. Results. The study of histological slides of mammary glands in women of different ages revealed that the developed mammary gland has a complex and heterogeneous ductal-lobular structure. The structural units of its functional (lactating) component are embedded within the stroma, which is composed of fibrous and adipose tissue in varying quantities and proportions. The ductal-lobular component forms segments or lobules of the mammary gland, which are conditionally separated by layers of connective tissue. The most variable component in the gland’s structure is the adipose tissue, which can be present in varying amounts and have different localization. The main manifestation of age-related changes in the structure of the mammary gland is atrophy and a decrease in the relative proportion of glandular tissue, accompanied by a reduction in size and compression of acini, loss of fluffy collagenous interlobular stroma, and its replacement by homogeneous dense collagen fibers with areas of hyalinosis and fibrosis, as well as multiple clusters of adipocytes. Fibrous strands and massive accumulations of adipose tissue occupy up to 90% of the gland’s volume. Conclusion. Studying the structural features of mammary glands of different types and the patterns of their age-related physiological involution will allow for the optimization of diagnostic criteria for age-related and pathological changes in women of different age groups during histological examination.